The First Steps of the Siberian Industrial-Cooperative Construction in the Context of the Transition to a New Economic Policy (1921-1923) - E. V. Borodulina (Научный диалог)
Brief description of the situation with the trade cooperation of Siberia by the beginning of 1921 is given in the article. Its organizational construction and regional peculiarities are analyzed in transition to the new economic policy. The activity of the Siberian regional artisanal union is considered. The question is raised about the struggle for influence on industrial cooperation. The causes of the crisis and the collapse of the Sibartelsoyuz system are investigated. The author comes to the conclusion about the inertia of the military-economic methods of guiding the cooperative production of handicraftsmen and artisans throughout the period under review. It is noted that the system of direct state administration in this sphere persisted until 1923. It shows the inability of Sibartelsoyuz to lead the cooperation, because of which the crisis of the artisanal system continued. The main sources of work were materials from the funds of the State Archives of the Russian Federation, the Russian State Archive of Economics and the State Archives of the Novosibirsk Region, some of which were first introduced into scientific use.